Digital communications - Haykin, Simon (New Jersey: John Wiley & Sons, 1988)
This book offers the most complete, up-to-date coverage available on the principles of digital communications. It focuses on basic issues, relating theory to practice wherever possible. Numerous examples, worked out in detail, have been included to help the reader develop an intuitive grasp of the theory. Because the book covers a broad range of topics in digital communications, it satisfies a variety of backgrounds and interests, and offers a great deal of flexibility for teaching the course. The author has included suggested course outlines for courses at the undergraduate or graduate levels.
Appendix A-H, 508-577p.
Keywords: Digital Communication; Computer Science